The significance of the emphasis in the dialogue of the brothers of Yusuf: An analytical rhetorical study - Al-Zahrani, Saadallah Saleh Matar (Journal of Humanities & Social Sciences, 2021)
This study aims to clarify the significance of the affirmation in the dialogue of the brothers of Joseph, peace be upon him, in the light of the science of semantics. Which makes the hypothesis that their constant feeling that they are under suspicion makes them confirm their words; so that its content would reach the hearts of their listeners, even if those listeners were not in denial of their words; This behavior made the emphasis in their dialogue the most prominent stylistic feature worthy of contemplation and study.This study came in two sections: the first is the theoretical one; It dealt with the emphasis in the Arabic language, its reasons, and the characteristics of the dialogical text; To take from this a knowledge base to move towards the analysis and interpretation of the noble verses that included the dialogue of the Joseph brothers, in the second topic, which is the applied part of the study; Where I extrapolated the noble surah and extracted from it the places that included the dialogue of Joseph’s brothers with their father mostly, and with the entourage of Al-Aziz sometimes, and with Al-Aziz at other times, and then with Joseph himself; target From that extrapolation, classification and analysis, arriving at the psychological significance of the use of emphasis in this intense manner in the dialogue of the brothers of Joseph, peace be upon him, and I interrogated the text itself first, then I used the sayings of the commentators in what I am about to analyze, and I found that they did not pay attention to what I meant; It is an indication of the emphasis on the emotional state of Yusuf’s brothers, with the exception of three modern interpretations in which a passing reference was made to this aspect that I made the subject of my care, and these interpretations are: Tafsir al-Manar, Liberation and Enlightenment, in the shadows of the Qur’an.
Keywords: affirmations of the news; the dialogue text; Yusuf's brothers; the psychological significance of the affirmation